2017
DOI: 10.1038/s41598-017-12087-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression meta-analysis in diffuse low-grade glioma and the corresponding histological subtypes

Abstract: Diffuse low-grade glioma (DLGG) is a well-differentiated, slow-growing tumour with an inherent tendency to progress to high-grade glioma. The potential roles of genetic alterations in DLGG development have not yet been fully delineated. Therefore, the current study performed an integrated gene expression meta-analysis of eight independent, publicly available microarray datasets including 291 DLGGs and 83 non-glioma (NG) samples to identify gene expression signatures associated with DLGG. Using INMEX, 708 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
4
17
0
Order By: Relevance
“…Moreover, several studies were highlighted by the computational approach of the impact of mutations in IDH1 like I147S, V444A, and D375Y and in IDH2 like N439D and R140G [27][28][29] ; using the same mechanism by which we carried out the sequencing of IDH1, IDH2 and TP53 genes, we were able to identify a few different amino acid substitutions in the IDH1, IDH2, and p53 proteins, such as IDH1 R132, IDH2 R173M, and p53 R175H, R158G, and K305N. 6,30 The IDH mutations ( Figure 3A and B) occurring in the catalytic site are likely to cause a loss of catalytic activity; these mutated genes encode for D2HG which is proposed to be an oncometabolite in the cytoplasm for IDH1 and in the mitochondria for IDH2; it competitively inhibits KG-dependent enzymes, including the TET family of 5-methylcytosine hydroxylases and the JmjC family of histones lysine Cancer Informatics demethylases, resulting in cell differentiation. 27,28,31,32 Thirumal Kumar et al 27,28 reveal that the drug therapeutics for D-2hydroxyglutarate dehydrogenase are very limited; therefore, understanding the nature of molecular structure caused by these mutations will serve as platform for the development of novel targets for new drug therapy for D-2-hydroxyglutaric aciduria.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, several studies were highlighted by the computational approach of the impact of mutations in IDH1 like I147S, V444A, and D375Y and in IDH2 like N439D and R140G [27][28][29] ; using the same mechanism by which we carried out the sequencing of IDH1, IDH2 and TP53 genes, we were able to identify a few different amino acid substitutions in the IDH1, IDH2, and p53 proteins, such as IDH1 R132, IDH2 R173M, and p53 R175H, R158G, and K305N. 6,30 The IDH mutations ( Figure 3A and B) occurring in the catalytic site are likely to cause a loss of catalytic activity; these mutated genes encode for D2HG which is proposed to be an oncometabolite in the cytoplasm for IDH1 and in the mitochondria for IDH2; it competitively inhibits KG-dependent enzymes, including the TET family of 5-methylcytosine hydroxylases and the JmjC family of histones lysine Cancer Informatics demethylases, resulting in cell differentiation. 27,28,31,32 Thirumal Kumar et al 27,28 reveal that the drug therapeutics for D-2hydroxyglutarate dehydrogenase are very limited; therefore, understanding the nature of molecular structure caused by these mutations will serve as platform for the development of novel targets for new drug therapy for D-2-hydroxyglutaric aciduria.…”
Section: Discussionmentioning
confidence: 92%
“…Meta-analysis of gene expression in PDAC. deGs with low but continuous expression levels in all profile datasets were defined as gained genes, and DEGs that disappeared in the meta-analysis but were expressed in individual analyses or in the meta-analysis resulting from experimental errors in the platforms were defined as lost genes (20,44,45). in total, one gained gene, unkempt family zinc finger-like (UNKL), which was weakly expressed in all datasets (eS, -0.25395), and 1,278 lost genes were identified.…”
Section: Numbers -------------------------------------mentioning
confidence: 99%
“…a meta-analysis, as a large-sample study, has an advantage in addressing this limitation due to its enhanced statistical power (19). Prior meta-analyses have been applied to study tumors to confirm deGs between tumor tissue and normal tissue in glioma (20,21), lung cancer (22), bladder cancer (23), breast cancer (24), osteosarcoma (25), liver cancer (26) and pancreatic cancer (27). In the present study, integrative meta-analysis of expression data (inMeX) was used to conduct a meta-analysis based on 11 qualified microarray datasets, with the aim to identify crucial deGs between Pdac samples and normal pancreatic samples that may serve as biomarkers for Pdac treatment and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed elevated CUL3 expression levels in oligodendroglial tumor tissues and demonstrated its potential as a prognostic biomarker in this malignancy. The upregulation of CUL3 and its prognostic value have been reported in LGG in previous studies, which also revealed its correlation with tumor onset [35]. Further studies should be carried out to explore the mechanisms underlying the role of CUL3 during cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 62%